Pemberdayaan Home Industry Pembuatan Tepung Sagu dalam Meningkatkan Perekonomian Keluarga: Studi Kasus Kelurahan Kwala Begumit Kecamatan Binjai Kabupaten Langkat - Amwa, Djauky Ridho; Sugianto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to find out how the Empowerment of Home Industry for Making Sago Flour in Improving the Family Economy (Case Study of Kwala Begumit Village, Binjai District, Langkat Regency). This research is a descriptive qualitative research, data collection methods are observation, interviews and documentation. The subject of this research focuses on sago factory founders, managers and workers. Data analysis techniques in this study were data reduction, data presentation, and periodic conclusions drawn during the study. The results of this study indicate that the existence of this home industry can create jobs for the people of the village of Kwala Begumit Village, Binjai District, Langkat Regency. It is very well realized that the development of the community's economy through the small and medium business sector has proven to help the community in their family's economic life by reducing the level of unemployment that occurs in many rural areas. This is one of the distinctive characteristics of the small industrial sector, by continuing to develop and empower the community's economy, it will be able to help with the problem of lack of jobs and the large number of unemployed people in the village of Kwala Begumit Village, Binjai District, Langkat Regency. The development of the home industry that occurred in Kwala Begumit Village, Binjai District, Langkat Regency can be said to have increased and has developed because this area is the area that has the most number of micro businesses. Keywords: Home Industry, Improving the Economy, Sago Flour